An Assessment of Academic Optimism among Science Students in Public Senior Secondary Schools in Lagos State, Nigeria - Oludipe, Bimbola D.; Dixon, Olujide O. (NIU Journal of Humanities; Vol 5 No 1 (2020): KIU Journal of Humanities, Vol. 5 No. 1, March 2020, 2020)
This study assessed academic optimism among science students in Lagos state public senior secondary schools. The study is a descriptive survey type of research. The sample consisted of 1,450 Senior Secondary School (SSS) II and 795 SSS III science students randomly selected from thirty (30) public schools in Lagos state. Data was collected by means of an Academic Optimism Survey Questionnaire (AOSQ). Findings showed that responses towards Faculty Trust (FT) and Academic Emphasis (AE) were positive but negative for Collective Efficacy (CE) among the science students. Also, findings revealed a positive and significant relationship between: Collective Efficacy (CE) and Faculty Trust (FT) (r=0.492, p<0.05) on one hand, and Faculty Trust(FT) and Academic Emphasis(AE) (r=0.604, p<0.05) on the other hand. However, a positive and insignificant relationship was observed between Collective Efficacy (CE) and Academic Emphasis (AE) (r=0.348, p>0.05).  In addition, (AE), (FT)and (CE) are significantly related among science students in public senior secondary schools in Lagos, The study recommended that to improve Collective Efficacy (CE) of science students, teachers should allow them to express themselves so they will be able to make their own decisions. Also, teachers should give regular feedback and appropriate remedial instructions to students that need it. Keywords : Academic Optimism, Science Students,  Collective Efficacy,  Faculty Trust,  Academic Emphasis, Senior Secondary Schools